THE CONCEPT OF THE EDUCATIONAL COMPUTER MATHEMATICS SYSTEM AND EXAMPLES OF ITS IMPLEMENTATION - Lvov, M.; Vinnyk, M. (Journal of Information Technologies in Education (ITE), 2015)
The article deals with the educational computer mathematics system, based in Kherson State University and resulted in more than 8 software tools to orders of the Ministry of Education,Science, Youth and Sports of Ukraine. The exact and natural sciences are notable among all disciplines both in secondary schools and universities. They form the fundamental scientific knowledge, based on precise mathematical models and methods. The educational process for these courses should include not only lectures and seminars, but active forms of studying as well:practical classes, laboratory work, practical training, etc. The enumerated peculiarities determine specific intellectual and architectural properties of information technologies, developed to be used in the educational process of these disciplines. Whereas, in terms of technologies used in the implementation of the functionality of software, they are actually the educational computer algebra system. Thus the algebraic programming system APS developed in the Institute of Cybernetics of the National Academy of Sciences of Ukraine led by Academician O.A. Letychevskyi in the 80 years of the twentieth century is especially important for their development.